Toward a Socioenvironinental Agenda for South A1nerica: Prospects for an environmental turn among Latin America's new progressive governments are mixed. Despite a reigning fossil fuel consensus, promising shifts are underway. - Svampa, Maristella (NACLA Report on the Americas, 2023)
Toward a Socioenvironinental Agenda for South A1nerica: Prospects for an environmental turn among Latin America's new progressive governments are mixed. In contrast, the new governments in Colombia and to a lesser extent in Chile represent hope for a "second-generation progressivism" in which democracy and socioenvironmental problems-namely the climate crisis and extractivism-could be treated within a comprehensive government program as cross-cutting priorities, rather than isolated issues. Argentina: A Third Kirchnerist Government's Response to Socioenvironmental Issues The October 2019 return of Peronism in Argentina was greeted with joy after the disastrous neoliberal government of Mauricio Macri (2015-2019). In December 2021, the national government supported provincial authorities who wanted to open the road to large-scale mining.